PERAN BOARDING SCHOOL DALAM PENDIDIKAN KARAKTER DI SMP KHALIFAH BOARDING SCHOOL - Moh Jailani; Kun Nurachadijat (Al-Mau'izhoh, 2023)
Education is the only means to change human behavior, morals and character. Only with education will a person's condition change for the better in all aspects of life. However, if we look at it today, the morale of the students is far toasty than fire. This reality does not show a significant change in the morals of students and is far from the goal of education itself. The purpose of this study was to determine the extent to which boarding schools instill honest, disciplined and independent characters in students. This research method is a descriptive qualitative method by providing an overview of what programs are carried out to instill these characters. The results of several programs launched by the Khalifah Boarding School Middle School show that there will be very significant change.